Pengembangan kreativitas dan partisipasi Mahasiswa PSR: Pembelajaran kolaboratif collective painting dalam pembuatan gambar dekoratif - Khalifah, Annisa Nurul; Salim, Agus Nur (Universitas Lampung, 2025)
Fine art learning usually only focuses on individual development. Whereas through art, students can also collaborate in creating a work. For this reason, as prospective educators, students of Fine Arts Education or PSR must have a strategy to create learning activities that can develop creativity as well as student participation. The research method used this time is a qualitative method with an experimental approach. The approach is done to explore directly about the process, results, and dynamics that arise during data collection. The data collection instrument in this research is participatory observation of four PSR students who practice drawing, both individually and in groups, besides that there are also interviews and literature studies to strengthen the assessment of observation results. The purpose of this research is to compare the effectiveness of the decorative drawing process using conventional techniques and collective painting techniques as an innovation in the development of learning methods, which is expected to inspire learning models for PSR students. The results of these observations have proven that creativity and participation increase when applying the collective painting method. This is evident when implementing collective painting practices, where they have more discussions and communication to work together in creating works of monumental size than with conventional methods, where they only work individually and focus on their respective works.Keywords: Collective painting, creativity, learning strategies, participation, visual arts education